Psychological Well-being, Psychological Distress and Emotional State in College Students according to their Level of Physical Activity - Villarrubia, Mariano D. (2023)
In this study, the general objective was to determine the influence of physical activity levels on psychological well-being, psychological distress, and emotional state in college students from Río Cuarto. For this, the quantitative approach was used, with a cross-sectional design, of a simple prospective ex post facto type. A sample of 200 college students was used, who were administered the Physical Activity Questionnaire, short version (IPAQ-SF), the Psychological Well-Being Scale for Adults (BIEPS-A), the Positive and Negative Affect Scale (PANAS), and the Anxiety and Depression scales of the Derogatis Symptom Inventory, Revised (SCL-90-R). Statistically significant differences were found in the levels of psychological well-being and positive affect, depending on the levels of physical activity reported by the participants. The most active students presented better levels in these two variables than their inactive peers. These data may be relevant to promote actions oriented towards the practice of physical activity in higher education institutions.